The Interaction of Wool Coat Length and Productivity in Karakul Sheeps - Klichev Zafar Safarovich (Research Parks Publishing LLC, 2021)
The article describes the role of wool in the animal body in the offspring of karakul sheep, the role of wool fiber length in the formation of wool productivity and the results of research on their differences.